Optimalisasi Produktivitas Batu Andesit Menggunakan Metode Quality Control Circle Untuk Memenuhi Target Produksi Batu Andesit 18.000 ton/bulan Pada PT Pebana Adi Sarana Nagari Manggilang Kec. Pangkalan Koto Baru Kab. Lima Puluh Kota, Provinsi Sumatera Barat - Rani anggraini; Adree Octova (Journals Mining Engineering : Bina Tambang, 2020)
Abstract. PT Pebana Adi  Sarana is a company engaged in andesite mining located in Lima Puluh Kota Regency. Andesite mining activities are carried out using the quarry mining method.PT Pebana Adi Sarana has a constant mounly production target of 18.000 tons/month. However, the realization of production for the august-september 2020 period was not achieved, namely ar 15.215,33 tons/month. Where the production achieved is only 84,5% og the target set by the company.This study uses the QCC method to increase production based on a paretto analisys of the main problem and the dominant cause of the not optimal production of minning equipment is 47% while on the conveyance 42% of the avaible working time. By making improvements to the working tim wasted with the QCC menthod the productivity increased to 44% for loading equipment and tranportation equipment bu 38% from the actual productivity. After encreasing the time wasted to be 93,79 hours/month for digging tolls and 81,09 hours/mont foe comveyances.Keywords : Excavator, DT Scannia, Productivity, Quality Control Circle, Paretto, Fishbone